Termodinâmica do modelo Bouncer: um gás unidimensional simplificado - Cespedes, André Machado [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this work we investigate some dynamical properties for an ensemble of particles in a dissipative bouncer model. The model consists of a classical particle (or an ensemble of them) colliding against a wall that oscillates as function of the time, under the action of a constant gravitational field. The equations that describe the complete model include two types of collisions: (i) direct and; (ii) indirect. There is a simplified version of the model which is equivalent to Chirikov's standard map. The map shows a transition from local to global chaos when the parameter reaches a critical value. The conservative model preserves the phase space area and, depending on the initial conditions as well as control parameter, can show unlimited growth of energy, a phenomenon known as Fermi acceleration. The phenomenon is suppressed by introducing dissipation via inelastic collisions. The transition between unlimited and limited growth of energy is described by scaling hypothesis. Such scaling leads to a generalized homogeneous function that provides two scaling laws, validated by well defined critical exponents. The analytical expression of the mean square velocity of particles leads to the calculation of these exponents of the transition, obtained independently of the simulations. An overlap of the curves Vrms vs. n validates the critical exponents obtained. The connection of the bouncer model with Thermodynamics is obtained by developing an expression for the Entropy, in agreement with the 3rd Postulate of Thermodynamics

Neste trabalho investigamos algumas propriedades dinâmicas para um ensemble de partículas no modelo bouncer dissipativo. O modelo consiste de uma partícula clássica (ou um ensemble delas), sob ação de um campo gravitacional constante, colidindo contra uma parede que oscila no tempo. As equações que descrevem o modelo completo abrangem dois tipos de colisões: (i) diretas e; (ii) as indiretas. Existe ainda uma versão simplificada do modelo que é equivalente ao Mapa Padrão de Chirikov. Este por sua vez exibe uma transição de caos local para caos global quando o parâmetro ε atinge um valor crítico. O modelo conservativo preserva área no espaço de fases e pode exibir crescimento ilimitado de energia, fenômeno conhecido como Aceleração de Fermi. O fenômeno é suprimido através da introdução de dissipação via colisões inelásticas. A transição entre crescimento ilimitado e limitado de energia é descrita através de hipóteses de escala. Estas conduzem a uma função homogênea generalizada que fornece duas leis de escala, validadas através dos expoentes críticos. A expressão analítica da velocidade quadrática média das partículas nos leva ao cálculo dos mesmos expoentes da transição, obtidos de forma independente das simulações. Uma sobreposição de curvas Vrms vs. n valida os expoentes críticos obtidos. A conexão do modelo bouncer com a Termodinâmica é obtida através do desenvolvimento de uma expressão para a Entropia, em concordância com o 3o Postulado da Termodinâmica
Keywords: Thermodynamics; Termodinamica; Caos determinístico; Leis de escala (Fisica estatistica)